2015
DOI: 10.1186/s12889-015-2579-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a national school-based Human Papillomavirus (HPV) vaccine campaign in Fiji: knowledge, vaccine acceptability and information needs of parents

Abstract: Background: In 2008 Fiji implemented a nationwide Human Papillomavirus (HPV) vaccine campaign targeting all girls aged 9-12 years through the existing school-based immunisation program. Parents of vaccine-eligible girls were asked to provide written consent for vaccination. The purpose of this study was to describe parents' knowledge, experiences and satisfaction with the campaign, the extent to which information needs for vaccine decision-making were met, and what factors were associated with vaccine consent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…[46][47][48] However, this conjecture has not been supported by studies that have reported no statistically significant increase in sexual behaviour and STIs in adolescents after HPV vaccination. 49,50 Although the acceptance of the HPV vaccine has been shown to be generally high in many countries [51][52][53][54][55] , these social concerns need to be considered if high coverage is to be achieved in Ghana.…”
mentioning
confidence: 99%
“…[46][47][48] However, this conjecture has not been supported by studies that have reported no statistically significant increase in sexual behaviour and STIs in adolescents after HPV vaccination. 49,50 Although the acceptance of the HPV vaccine has been shown to be generally high in many countries [51][52][53][54][55] , these social concerns need to be considered if high coverage is to be achieved in Ghana.…”
mentioning
confidence: 99%
“…In some regions, "community influencers" (e.g., teachers, health workers, and other community members) are necessary for helping to raise awareness of cervical cancer as it is reported to play more important role than information given from health providers. Although the need of media in promoting the vaccines it is found that media has sometimes given negative perceptions like the adverse reactions (24) that would act as a hinder to willingness. Apparently, media does not influence the willingness to vaccinate.…”
Section: Knowledge Of Hpv Vaccinesmentioning
confidence: 99%
“…Race is one of the factors, for instance, a study on African American girls shows vaccination series initiation and completion were lower than the national average (23) . In 2008, survey and campaign were conducted in Fiji (24) showed the participants knowledge about HPV were low prior to the campaign. Where only as low as 10.2% of the participants have heard about HPV vaccines, 21.2 % reported having heard of cervical cancer, and the majority of these knew someone who had the disease.…”
Section: Knowledge Of Hpv Vaccinesmentioning
confidence: 99%
“…The countries included: Turkey, Vietnam, Fiji, Malaysia, Indonesia, Eastern India, Thailand and China. From all articles in this geographical area, parental acceptability ranged from 44%-96%, with significant increases in acceptability in China, Fiji and Vietnam if some sort of government program was established in support specifically for the HPV vaccination (Alsaad, Shamsuddin, & Fadzil, 2012;Basu & Mittal, 2011;Dinh et al, 2007;Jaspers, Budiningsih, Wolterbeek, Henderson, & Peters, 2011;Kilic, Seven, Guvenc, Akyuz, & Ciftci, 2012;Kruiroongroj, Chaikledkaew, & Thavaorncharoensap, 2013;Madhivanan et al, 2009;Madhivanan et al, 2014;Mairaing, Suwannarakark, THaweekul, & Poomtavorn, 2012;Songthap, Pitisuttithum, Kaewkungwal, Gungladda, & Bussaratid, 2012;Vincente et al, 2015;Wang et al, 2015;Wong, 2009;Zhang et al, 2013). The most dominant predictor for parental acceptability in these countries was higher education and increased knowledge specifically around HPV, cervical cancer and protective measures the vaccine offers.…”
Section: Parent Awareness About Hpv and Acceptability Of The Hpv Vaccmentioning
confidence: 99%
“…Research conducted in similar settings demonstrated caretaker HPV vaccine acceptance for their daughters between 44-96%. The most common reasons for caregivers (predominantly female) to refuse the HPV vaccine for their daughters included, fears about vaccine efficacy and safety, low education and awareness about HPV and its association to cervical cancer and the high cost of the vaccine (Mouallif et al, 2014;Perkins et al, 2011;Vincente et al, 2015;Zhang et al, 2013).…”
Section: Acceptability Of Hpv Vaccine: Childrenmentioning
confidence: 99%